2001
DOI: 10.1002/jcb.1280
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear estrogen receptor II (nER‐II) is involved in the estrogen‐dependent ribonucleoprotein transport in the goat uterus: II. isolation and characterization of three small nuclear ribonucleoprotein proteins which bind to nER‐II

Abstract: Three proteins of a goat uterine small nuclear ribonucleoprotein (snRNP) fraction, which bind to nuclear estrogen receptor-II (nER-II) have been isolated and purified. These are the p32, p55, and p60 of which p32 is the major nER-II binding protein. Indirect evidence reveals that p32 binds to the nuclear export signal (NES) on the nER-II. nER-II is a snRNA binding protein while p32 does not bind to the RNA. nER-II along with p32 and p55 form an effective Mg(++)ATPase complex, the activation of which appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The data presented in this and the companion paper [Sebastian and Thampan, 2001] is a natural extension of the experimental data reported earlier [Thampan, 1985, 1988, 1989]. A clear lead has been obtained with reference to the biological functions of nER‐II in view of the localization of nER‐II in small nuclear ribonucleoproteins (snRNPs).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…The data presented in this and the companion paper [Sebastian and Thampan, 2001] is a natural extension of the experimental data reported earlier [Thampan, 1985, 1988, 1989]. A clear lead has been obtained with reference to the biological functions of nER‐II in view of the localization of nER‐II in small nuclear ribonucleoproteins (snRNPs).…”
supporting
confidence: 63%
“…Earlier studies had reported on the activation of a nuclear Mg 2+ ‐dependent ATPase prior to the RNP exit from the nuclei following exposure to estradiol. The nature of the protein complex involved in this ATPase activity has also been recognized in the companion paper [Sebastian and Thampan, 2001].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation